Analisis Hambatan Pembelajaran Biologi Materi Jaringan Tumbuhan Dalam Pelaksanaan Kurikulum 2013 Di SMA - Evi Susilawati; Khausar Khausar; Rufa Hera (research, training and philanthropy institution Natural Aceh, 2020)
Abstract: This study aims to determine: 1) barriers to learning biology of plant tissue material in the implementation of 2013 class XI curriculum at SMA Negeri 1 Meureubo; 2) factors inhibiting the learning of plant tissue biology in the implementation of the 2013 XI class curriculum at SMA Negeri 1 Meureubo. This research uses qualitative. From the results of the study, there are obstacles faced by class XI teachers of SMA Negeri 1 Meureubo in the learning process of plant tissue biology in the implementation of the 2013 curriculum, which are the availability of books and supporting infrastructure which are inadequate, too short training, limited use of media, and assessment is so difficult and requires a lot of time. Abstrak: Penelitian ini bertujuan untuk mengetahui: 1) hambatan pembelajaran biologi materi jaringan tumbuhan dalam pelaksanaan kurikulum 2013 kelas XI SMA Negeri 1 Meureubo; 2) faktor-faktor hambatan pembelajaran biologi materi jaringan tumbuhan dalam pelaksanaan kurikulum 2013 kelas XI SMA Negeri 1 Meureubo. Penelitian ini menggunakan kualitatif. Dari hasil penelitian maka terdapat hambatan-hambatan yang dihadapi guru kelas XI SMA Negeri 1 Meureubo dalam proses pembelajaran biologi materi jaringan tumbuhan pada pelaksanaan Kurikulum 2013 adalah ketersediaan buku dan sarana prasarana pendukung yang kurang memadai, pelatihan yang terlalu singkat, penggunaan media yang terbatas, serta penilaian yang begitu sulit serta membutuhkan waktu yang banyak.